ANALISIS KONFLIK PENYELESAIAN BULLYING DI SMP SYUBBANUL WATHON TEGALREJO MAGELANG: ANALISIS KONFLIK PENYELESAIAN BULLYING DI SMP SYUBBANUL WATHON TEGALREJO MAGELANG - Ahmad Fuad Hasyim; Laili Syarifa; Rizky Putri Antiwi (LP2M IAIN Sultan Amai Gorontalo, 2025)
Bullying in school environment is a serious problem that has negative impacts on students’ psychological, social, and academic development. Syubbanul Wathon Junior High School Tegalrejo Magelang faces this challenge with increasing cases of bullying, both physically and verbally. This study aims to resolve conflicts due to bullying based on Mitchell’s conflict management theory, with the main stages: recognition, analysis, decision making, implementation, monitoring, and evaluation. This study uses qualitative descriptive method with interviews, observation, and documentation as data collection techniques. The results of the study show that the resolution strategies implemented include strict supervision, guidance and counseling, socialization of the dangers of bullying, and mediation between the parties involved. The resolution process involves various parties, including BK teachers, homeroom teachers, and parents, with a mediation and education-based approach. This approach has proven effective in reducing bullying rates and creating a more conducive school environment. The implementation of Mitchell’s theory in conflict resolution shows that the active involvement of all elements of the school is very important in overcoming bullying systematically and sustainably.